Experiences of family members caring for a sibling with mental illness in Giyani, Limpopo - Tintswalo Vukeya; Annie Temane; Marie Poggenpoel (AOSIS, 2022)
Background: Mental illness is a serious condition affecting the diagnosed individual and all family members. Family members caring for a sibling with mental illness encounter severe challenges, which, if unresolved, becomes a burden they carry for the rest of their lives. Objectives: The purpose of the study was to describe family members' experiences caring for a sibling with mental illness in Giyani. Method: A qualitative, exploratory, descriptive and contextual research design was used. Eight family members caring for a sibling with mental illness were purposively sampled. Data were collected through in-depth phenomenological interviews, and data were analysed using thematic coding, and an external coder was consulted. Results: The study's findings revealed that family members caring for a sibling with mental illness experienced significant challenges. The three themes that emerged after data analysis were the following: caring for a sibling with mental illness was an overwhelming experience; family members experience emotional instability as a result of caring for their sibling with mental illness and family members need support in caring for their sibling with mental illness. Conclusion: The findings indicated that family members need support in caring for a sibling with mental illness. Family members would cope better with support from extended family, healthcare professionals in mental health and the community; this will reduce the burden of caring for a sibling with mental for family members. Furthermore, the availability of resources can assist in facilitating family members' mental health. Contribution: This study could make an impact in psychiatric nursing practice, nursing education in promotion of support for family members for a sibling with mental illness.